Improved modulation method with reduced switching frequency for OW‐PMSM system with common DC bus - Heng Nian; Chenhui Ruan; Wei Hu; Dan Sun (Electronics Letters, 2019)
To reduce the switching frequency of open‐winding permanent magnet synchronous motor (OW‐PMSM) system with a common DC bus, this Letter proposes a novel modulation method. In this method, the independent modulation is implemented in each phase to generate the reference voltages in the abc reference frame, where only one bridge arm has switching actions. Compared with the existing modulation methods for OW‐PMSM system, the total switching actions within one PWM period can be remarkably reduced to 6 with the control target of the zero‐sequence current suppression achieved, and the modulation range can be kept unchanged. The experimental results validate the availability of the proposed modulation method for OW‐PMSM system.